Application of User-Centered Design Method in Redesign of The iPusnas Digital Library Interface Based on User Experience Evaluation - Karin, Ayu Andhini Mutya; Wati, Seftin Fitri Ana; Fitri, Anindo Saka (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2024)
The low interest in reading in Indonesia is due to several inhibiting factors. One of the biggest obstacles is the limited access to libraries, books, and other literacy resources. Therefore, the National Library has made efforts to develop digital library services, namely iPusnas. However, this digital transformation does not always run smoothly. Some users have reported that the iPusnas app interface is considered too old-fashioned, boring, and confusing. Some users also complained about the lack of sort and filter features, book grouping, and so on. Therefore, a redesign is needed. This study uses the User-Centered Design (UCD) method to identify all user needs and issues and to create a solution for the iPusnas interface. Through two iterations of testing, the results of the first iteration showed a System Usability Scale (SUS) score of 82.72 out of 100 and a Net Promoter Score (NPS) of 55.56 out of 100. The second iteration showed a System Usability Scale (SUS) score of 86.27 out of 100 and a Net Promoter Score (NPS) of 73.33 out of 100. Overall, the evaluation results improved and met user needs.